Crimes and Determinants of Young Criminals: A Study of Interior Sindh, Pakistan - Hyder Ali Memon; Muhammad Akhter Arain; Hadi Bakhsh Kalhoro; Saqib Ali Shaikh (Journal of Management Practices, Humanities and Social Sciences, 2022)
The purpose of the study is to identify the crimes perpetrated by young offenders in the interior districts of Sindh, including Shikarpur, Sukkur, Dadu, and Ghotki, as well as to investigate the underlying causes of criminal behavior. This qualitative study was undertaken by collecting FIRs from four districts using random sampling. The sample consists of 485 FIRs of convicted young male offenders from 2019 to 2020. The study found that youth are involved in various crimes such as murder, rape, larceny, assault, drug/alcohol consumption, and illegal weapon possession. In addition, the study's findings identified the factors that inspire young offenders to commit crimes, including poverty, land conflicts, tribal feuds, provocation, retaliation, sexual passion, and thrill. Consequently, illegal activities, as opposed to more constructive ones, are gaining popularity among the younger generation; therefore, the study suggests establishing a parental care and control program to improve educational and training facilities, increase employment opportunities, decrease the availability of dangerous weapons and drugs and alternative methods of crime prevention should be implemented.